An Analysis of Students’ Perception of Difficulties Speaking English: A Case Study at 11th Grade Students’ of SMAN 7 Kota Serang - Afifah Nabilah; Innaki Fatimah Azzahra; Nurul Mahdiyyah; Riska Hanifah (Jurnal Kajian Ilmu Pendidikan (JKIP), 2023)
The problems raised in this research were based on field conditions located at SMAN 7 Serang City. Based on the class observations that have been carried out, several problems have been found. Among them, are students'' passivity in English classes, lack of interaction and communication using English during class, and students'' disinterest in speaking in English. However, in reality, speaking is an important aspect of learning a language. This is considered the key to individual success in learning a language. To assess whether he is proficient or not. In this research, the researcher tries to find the difficulties of students in speaking English by their perception. Then the data is collected by sharing the questionnaire with Thirty-one students in 11th grade and doing interviews with some students to know their perception of difficulties in speaking English. As for the results obtained from the questionnaire and interview activities, they generally regretted the teacher's learning methods, which in practice rarely used English in delivering material and teaching. On average, they think conversation practice can improve their English-speaking skills. Apart from that, another factor is the limited facilities and support for them in speaking English. Only one of them took an English course outside of school. Some conclusions from interview activities and distributing questionnaires in class 11 of SMAN 7 Kota Serang for data collection carried out by researchers include: 1. Lack of awareness of the importance of English, desire, and self-confidence in grade 11 students of SMAN 7 Kota Serang affects their ability to speak English which is accompanied by their anxiety about speaking English. 2. The influence of teachers'' teaching methods and lack of motivation influence students'' speaking abilities, where in their teaching methods teachers very rarely interact and communicate using English. So, students are also not motivated and encouraged to speak English in class. 3. Lack of application of English in students'' daily lives so that they are not used to using English in class or outside of class. These three factors are proven to influence students'' English-speaking abilities. The most important difficulty they face is the problem of pronunciation where the difficulty is based on the underlying factors.